Range extension for three species of South American freshwater crabs (Crustacea: Decapoda: Trichodactylidae) - Collins, Pablo Agustin (2009)
New sampling programs have extended the distribution of three species of freshwater crabs (family Trichodactylidae): Dilocarcinus septemdentatus and Sylviocarcinus pictus from the Amazon basin to southern South America, and S. australis, from the north of Argentina southwards. The three species are now found in the floodplain of the middle Paraná River (31°39´S, 60°45´W). The extension of their distribution is approximately 500 km and 2000 km further south. The number of freshwater crab species in the alluvial valley of the Paraná River has increased by 30% with these new records.